Factors associated with quality of life in children with asthma living in Scotland. Issue 5 (15th December 2015) - Taminskiene, Vaida; Mukhopadhyay, Somnath; Palmer, Colin; Mehta, Anil; Ayres, Jon; Valiulis, Arunas; Turner, Steve W.
Summary: Introduction: Asthma affects children's quality of life (QoL) but factors associated with QoL are not well understood. Our hypothesis was that there are factors linked to QoL which are amenable to treatment or environmental modification. Methods: QoL was ascertained in a study designed to link environmental exposures to asthma outcomes. Univariate and multivariate analysis were used to determine which factors are associated with QoL. Results: There were 553 children with asthma where QoL was determined, mean age 10.3 and 312 (58%) were boys. The median QoL score was 5.9 (interquartile range 4.6, 6.8). In the multivariate model, asthma severity (as evidenced by British Thoracic Society, BTS, treatment step), smoking exposure, socioeconomic status and rhinitis were associated with the QoL score. QoL score was reduced by (i) 30% [95% confidence interval 20, 39] for those on BTS step 4 compared to BTS step 1 treatment (ii) 11% [2, 19] for children with ≥ two resident smokers with reference to no resident smokers (iii) 3% [1, 5] for each quintile difference in deprivation compared to the most affluent and (iv) 9% [4, 14] for children with rhinitis compared to no rhinitis. Conclusions: The QoL for children with asthma in the UK is generally good. Clinicians caring children with asthma should consider routinely asking about smoke exposure and hayfever symptoms in addition to assessing asthma control.Pediatr Pulmonol. 2016;51:484–490 . © 2015 Wiley Periodicals, Inc.